Reproductive coercion and intimate partner violence among rural women in Côte d'Ivoire: a cross-sectional study. - Falb, Kathryn L; Annan, Jeannie; Kpebo, Denise; Gupta, Jhumka (African journal of reproductive health, 2014)
A growing body of U.S.-based research demonstrates that reproductive coercion is an important consideration regarding the negative health impacts of intimate partner violence (IPV). However, less work on IPV and reproductive coercion has been done in West African settings. Cross-sectional data of 981 women who participated in the baseline survey of a randomized-controlled trial in rural, Côte d'Ivoire in October 2010 were analyzed for specific reports of reproductive coercion. Half (49.8%) of all women reported lifetime physical or sexual IPV, and nearly 1 in 5 (18.6%) reported experiencing reproductive coercion. In the final adjusted analyses, lifetime IPV was associated with a 3.7 increase in odds of reporting reproductive coercion (95% CI: 2.4-5.8) compared to women who did not report such victimization. Study findings underscore the importance of reducing IPV in order to improve reproductive health among women in rural Côte d'Ivoire.
Keywords: Adult; Coercion; Cote d'Ivoire; Cross-Sectional Studies; Female; Humans; Interpersonal Relations; Middle Aged; Reproductive Health; Risk Factors; Rural Population; Sexual Behavior; Sexual Partners; Spouse Abuse; Women